Exposureassessmentof greenhouseworkerswithanti-cholinesterase pesticides by biological monitoring - Sh Bakand; Y Dehghani; M Gohari; M.H Mosadegh; S.J Mirmohammadi (Salāmat-i kār-i Īrān, 2012)
Background and Aims: Organophosphate compounds are the most popular insecticides with the widespread application in pest control. These toxic compounds interfere with the blood cholinesterase and inhibit the cholinestarse activity.Measurement of Cholinesterase activity is widely used for diagnosis of poisoning and adverse effects caused by pesticides. Green-house workers are one of the important occupational groups with the high risk of poisoning with organophosphate and karbamat pesticides .The purpose of this study was to assess the exposure of green-house workers with anti-cholinesterase toxic compounds by measuring the blood cholinesterase activity using electrometric method.   Methods: This research is a descriptive cross sectional study that carried out on farmers of the cucumber green-houses . In this study, 40 workers were selected and their blood cholinesterase enzyme activity were measured using electrometric method . In electrometric method the reduction of cholinesterase activity can be measured through recording the changes of blood pH induced by anticholinestrase agents . The results were analyzed by version16 of spss software.   Results: Based on the obtained results the amount of erythrocyte cholinesterase enzyme inhibition was between 1 / 77% to 35 / 4% and the mean and standard deviation was 23 / 2% ±9 / 68.   Similarly, the amount of plasma cholinesterase enzyme inhibition was between 1% to 28% and the mean and standard deviation was equal to 16/57 ±7 / 92.   Following the analysis of results 25% (n=10) of the workers were identified with no poisoning, 17.5% (n = 7) with minor poisoning , 55% (n=22) with moderate poisoning and 2.5% (n=1) with severe poisoning.     Conclusion : Organophosphate poisoning has been reported as the third cause of poisoning and also the leading cause of poisoning deaths in our country.Therefore, considering the results of this research and the importance of the evaluation of workers exposure to organophosphate pesticides it can be stated that the use of electrometric method is a valuable tool for biological monitoring of exposed populations . As this method is simple, portable and not expensive and at the same time provides high precision , it has a potential to be applied for screeningandearlydiagnosisof organophosphate poisonings inlarge-scale studies.